2014
DOI: 10.5039/agraria.v9i1a3466
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil fertility and mineral nutrition of mango orchards in São Francisco Valley, Brazil

Abstract: This research aimed to analyse the soil fertility changes and macronutrient concentration in mango plantations in Petrolina, Pernambuco, Brazil. Samples of soil were collected at depths of 0-20 and 20-40 cm, and leaves of mango trees during vegetative growth were collected from 11 areas with different cultivation time spans (6, 7, 8, 9, 10, 11, 14, 16, 17, 19, and 26 years). Nearby areas under natural vegetation were sampled for reference. The chemical characteristics of soil evaluated were: pH; P, K, Ca, Mg; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Moreover, the soils from the semi-arid region generally have a sandy texture, and its adsorption sites (colloids) are easily saturated, which favors the increase in the mobility and leaching of K, as it is a monovalent cation (SANTOS et al, 2015). Silva et al (2014) confirmed this hypothesis in a study of soil fertility changes in mango orchards in the São Francisco valley region, demonstrating that the movement of the nutrients is favored by daily irrigation practices and the sandy soil texture, similar to observations in the three areas of the present study, contributing to its high variability.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the soils from the semi-arid region generally have a sandy texture, and its adsorption sites (colloids) are easily saturated, which favors the increase in the mobility and leaching of K, as it is a monovalent cation (SANTOS et al, 2015). Silva et al (2014) confirmed this hypothesis in a study of soil fertility changes in mango orchards in the São Francisco valley region, demonstrating that the movement of the nutrients is favored by daily irrigation practices and the sandy soil texture, similar to observations in the three areas of the present study, contributing to its high variability.…”
Section: Resultssupporting
confidence: 90%
“…Other authors have also found high variability for K + content (Oliveira et al, 2015;Rodrigues & Corá, 2015). This can be due to some factors such as: 1) frequent application of fertilizers (Richart et al, 2016): as in the São Francisco River Valley, fertilization with this nutrient is performed by fertigation, using the most soluble forms (Silva et al, 2014) --------------- ---------------0.0-0.2 m-----------------------------0.2-0.4 m--------------Ca 2+ (cmol c dm -3 ) 6.00 3.00 In general, the variables of the Mandacaru area showed the lowest range values in both layers (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to correct the Ca 2+ level, which is above the optimum values since its highest content is found in mango leaves (Silva et al, 2014), and calcium deficiency can depreciate the quality of the fruit, as low concentration of leaf Ca is associated with the incidence of internal collapse in mango (Almeida et al, 2015). Therefore, higher calcium content in the fruit slows ripening and senescence, by reducing respiration, ethylene evolution and loss of fresh weight, extending post-harvest life and fruit quality of mango (Aular & Natale, 2013;Hojo et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…These values probably exceed plant requirements, which Schmitt et al Factor 2 showed high positive and negative loadings on pH (0.77) and Al (-0.93). The opposite association between P and sand content confirms that P movement towards deep layers is mainly governed by soil texture (Silva et al, 2014). Therefore, the high and continuous application of P in these soils increases the potential of P leaching and contamination of surface and underground waters (Pizzeghello et al, 2011).…”
Section: Journal Of Soil Science and Plantmentioning
confidence: 98%
“…Therefore, studies on the effects of agricultural practices on soil quality and sustainability are of paramount importance, especially for crops with intensive chemical input (Serrano et al, 2017). (Silva et al, 2014). These changes can affect both crop yield and the quality of the soil environmental (Fernández-Calviño et al, 2010;Wightwick et al, 2013;Duplay et al, 2014;Silva et al, 2014;Brunori et al, 2016;Preston et al, 2016), resulting in either improvement of the soil properties or accelerated soil degradation (Jiao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%